THE INFLUENCE OF GREEN MARKETING, SOCIAL MEDIA MARKETING AND PRODUCT QUALITY ON GENTLE GEN PRODUCT PURCHASE DECISIONS - Sandra, Napalia; Nuryah, Aminah (Al-Mubin, 2025)
This study aims to analyze the influence of green marketing, social media marketing, and product quality on the purchase decision of Gentle Gen plant-based detergent products. Primary data was collected through an online questionnaire from 160 respondents who were users of Gentle Gen products and were active on social media. The results of the study show that these three independent variables simultaneously have a positive and significant effect on purchasing decisions. Green marketing contributes to shaping consumer awareness of environmentally friendly products, social media marketing increases consumer interaction and loyalty, and product quality is the main factor influencing purchase decisions. This research provides recommendations for companies to continue to optimize their sustainable marketing strategies to win market competition